Analysis of cytotoxic T-lymphocyte-associated antigen-4 and MMP-9 genes’ methylation and their expression profiles with risk of non-alcoholic fatty liver disease - Tamandani, Dor Mohammad Kordi (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: To investigate the effect of promoter methylation of cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) gene and matrix metalloproteinases (MMPs) on the risk of non-alcoholic fatty liver disease (NAFLD). MATERIALS AND METHODS: CTLA-4 and MMP-9 promoter methylation were investigated using a methylation-specific polymerase chain reaction (MS-PCR) in blood samples taken from 80 NAFLD individuals and 95 healthy controls. The expression levels of CTLA-4 and MMP-9 were also assessed in 10 blood and 9 liver tissues mRNA samples from NAFLD patients. These cases were compared to the blood (n = 10) samples of healthy controls with real-time quantitative reverse transcriptase PCR. RESULTS: No significant relationship was found for methylation of CTLA-4 and MMP-9 between cases and controls. The relative expression of CTLA-4 and MMP-9 mRNA in NAFLD was not significantly different compared to healthy control samples. CONCLUSION: For the first time, our outcomes indicate that the methylation status of CTLA-4 and MMP-9 genes has no significant function on the process of NAFLD.